Safety and Immunogenicity of a Quadrivalent Meningococcal Conjugate Vaccine (MenACWY-D) in Children 9–23 Months of Age in Russian Federation: Results of Russian Part of International Study in Russia and India - O. A. Perminova; V. V. Romanenko; V. Yu. Rodnikova; S. M. Kharit; Y. Thollot; V. Bosch-Castells; A. V. Goldstein (Эпидемиология и вакцинопрофилактика, 2020)
Aim. Assessment of tolerability, safety and immunogenicity of the 4-valent conjugated meningococcal MenACYW-D vaccine, administered 2 times to children 1–2 years of age in the Russian Federation.Study participants. 100 children aged 9–17 months not previously vaccinated against meningococcal infection.Methods. Two doses of the MenACYW-D vaccine were administered intramuscularly at intervals of 3–6 months. Antibody titers for meningococci of serogroups A, C, W, and Y were determined using a serum bactericidal assay in the presence of human complement before the 1st vaccination and 28 days after the 2nd vaccination. Participants with titers ≥ 1:8 were considered protected from meningococcal infection caused by the corresponding serogroup of meningococci.Results. After two vaccinations, the level of seroprotection in relation to these four serogroups of meningococci was achieved in 92.9–99.0% of vaccinated children. No immediate adverse events were reported after any of the 2 doses of the vaccine studied. The frequency of local and general expected adverse reactions after any of the 2 doses of the vaccine was 45% and 40%, respectively, in terms of severity they were mostly weak and disappeared within 3 days. In general, there was no increase in the reactogenicity of the vaccine after administration of the 2nd dose compared to the 1st dose. Unexpected adverse events were recorded in 10% of the study participants, of which only one (diarrhea that stopped within one day) at the conclusion of the research physician was a causally related with the vaccine. None of the adverse events led to the early termination of participation in the study. One serious adverse event has been reported, which the physician has identified as not having a causal relationship with the vaccine being studied.Conclusions. Two dose immunization with the MenACWY-D vaccine in children 1–2 years of age in the Russian Federation was safe, well tolerated, and induced a pronounced bactericidal humoral immune response against meningococci of serogroups A, C, W, and Y.